2015
DOI: 10.1002/csr.1366
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Enterprises and Corporate Social Responsibility Practice: A Swedish Perspective

Abstract: The purpose of this paper is to investigate the characteristics of corporate social responsibility (CSR) practice in Swedish small and medium-sized enterprises (SMEs). A case study approach is used to investigate the CSR perception, motivation, and activities of two Swedish SMEs. This paper indicates that two Swedish SMEs studied adopt a profitseeking rather than a profit-sacrificing CSR approach. Furthermore, the paper argues that the perception, the motivation, and part of the CSR activities are well incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 59 publications
6
113
1
2
Order By: Relevance
“…Pan, Sha, Zhang, and Ke [18] observed that employee responsibility and environmental responsibility have significant positive relationships with corporate financial performance. Lee, Herold, and Yu [55] suggested that SMEs are motivated to pursue CSR activities when they perceive a business benefit and value for the company. Further, SMEs engage in community CSR when they perceive benefits such as better business and improved customer loyalty.…”
Section: Financial Performancementioning
confidence: 99%
“…Pan, Sha, Zhang, and Ke [18] observed that employee responsibility and environmental responsibility have significant positive relationships with corporate financial performance. Lee, Herold, and Yu [55] suggested that SMEs are motivated to pursue CSR activities when they perceive a business benefit and value for the company. Further, SMEs engage in community CSR when they perceive benefits such as better business and improved customer loyalty.…”
Section: Financial Performancementioning
confidence: 99%
“…In addition, there is most important to develop social responsibility of the SME (e.g. Lee et al 2015). The experience of Japan shows that the introduction of training programs for entrepreneurs on CSR, allows them to subsequently pursue an effective CSR policy, improve management and business environment (Makoya 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Related to a firm's values and capabilities are the entrepreneur's values and personal commitments, which can be linked to a higher level of environmental concern [61] because their attitudes are directly connected to corporate social activities [37]. The approach of small firms to ER is different from that of large firms in that it is personalized and informal.…”
Section: Environmental Responsibility Driversmentioning
confidence: 99%
“…Therefore, following a recent call to study the pro-environmental attitudes of SME entrepreneurs [37], the present paper seeks to examine the environmental responsibility of European SMEs within the water and waste sector and to analyze the motivations that lead them to develop broader environmental management.…”
Section: Introductionmentioning
confidence: 99%